Penerapan Metode SMARTER Pada Penentuan Media Literasi Pembelajaran Anak Berkebutuhan Khusus - Paramadina Mulya Majid; St Hajrah Mansyur; Harlinda L (Universitas Budi Darma, 2022)
Children with Special Needs (ABK) are part of society that must be empowered, both from their physical and mental limitations. In learning activities, especially for abk, they need learning media tools. There are 4 types of abk, namely Deaf, Visually Impaired, Deaf and Deaf. There are many learning media that can be used to increase the potential of abk students at SLB, but the school does not know the learning literacy media that suits the needs of students. This study aims to provide recommendations for learning media for website-based ABK students by considering three aspects of the criteria, namely academic assessment, non-academic assessment, and developmental assessment. The method used in decision making is the Simple Multi Attribute Rating Technique Exploiting Rank (SMARTER). Weighting in the SMARTER method uses the Rank Order Centroid (ROC) formula. The results of determining abk learning literacy media using the SMARTER method from 52 ABK students obtained media recommendations that can be given by students based on the severity level determined based on the final grade range. Meanwhile, based on the results of the questionnaire assessment to 14 respondents consisting of 1 principal and 13 teachers, it showed that the results of testing the system with the blackbox testing method obtained data for interface aspects as much as 88%, application performance 91%, database 90%, missing / damaged functions 46% and initialization 94%. Thus, the overall average application produced an index of 82% which is included in the good criteria.